Sustainable Tourism Competencies Through Digital Marketing Education: Evidence from Indonesia and Thailand - Aditya Yudanegara; Louie A. Divinagracia; Andhi Sukma (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Digitalisation and sustainability are reshaping tourism and higher education in ASEAN; however, evidence linking university digital marketing education to sustainable tourism competencies remains limited, particularly in cross-country contexts.Purpose: This study examines how digital marketing education, experiential learning, and technology acceptance shape human capital development and sustainable tourism competencies, tests the mediating role of human capital, and compares Indonesia and Thailand.Design/methodology/approach: A sequential explanatory mixed-methods design was used. Survey data were collected from 300 students and lecturers enrolled in tourism and marketing programs (Indonesia n=150; Thailand n=150) and analysed using PLS-SEM, including mediation and multi-group tests. Follow-up interviews and focus groups were thematically analysed to explain quantitative patterns.Findings/Results: Digital marketing education and experiential learning significantly enhance human capital development, which strongly predicts sustainable tourism competencies. The association between digital marketing education and competencies is modest. Technology acceptance directly and strongly predicts competencies but shows a negligible relationship with human capital. Experiential learning's direct link to competencies is weak or negative; however, its indirect contribution through human capital is positive. Mediation through human capital is supported for digital marketing education, partially for experiential learning, and not for technology acceptance. Multi-group analysis indicates a larger experiential learning effect on competencies in Thailand.Conclusion: Sustainable competencies improve when digital marketing education and scaffolded experiential learning strengthen human capital, and when technology adoption aligns with sustainability-oriented pedagogy.Originality/value (State of the art): The study advances an integrated Human Capital–Experiential Learning–TAM/TPACK perspective and offers actionable guidance for ASEAN curriculum harmonisation aimed at strengthening sustainability-oriented digital marketing competencies. Future research should test the model longitudinally and evaluate measurement invariance and institutional readiness. Keywords: ASEAN, digital marketing education, human capital development, sustainable tourism competencies, technology acceptance